PROBLEMS OF FUNCTIONAL DISCOURSE ANALYSES (Scientific journal of the Fergana State University, 2023)
The article reflects semantic, pragmatic or rhetorical discourse functions related in many ways to the interactional and socio-cultural functions. They always require a socio-cognitive interface, that is, episodic models of specific socio-cultural events and shared general knowledge or attitudes about societal structures, which both can be mapped on or constrain the cognitive representations that underlie a specific discourse.